2008
DOI: 10.1016/j.neuron.2008.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Direction Selectivity in the Retina Is Established Independent of Visual Experience and Cholinergic Retinal Waves

Abstract: Direction selectivity in the retina requires the asymmetric wiring of inhibitory inputs onto four subtypes of On-Off direction-selective ganglion cells (DSGCs), each preferring motion in one of four cardinal directions. The primary model for the development of direction selectivity is that patterned activity plays an instructive role. Here, we use a unique, large-scale multielectrode array to demonstrate that DSGCs are present at eye opening, in mice that have been reared in darkness and in mice that lack chol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
154
7
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 124 publications
(187 citation statements)
references
References 60 publications
24
154
7
2
Order By: Relevance
“…In contrast to our results reported here, previous reports from our laboratory that were based on multi-electrode array (MEA) recordings indicated that the cardinal distribution of preferred directions was established at eye-opening [5]. One potentially important difference is that the current study was the use of light stimulation of cones dominated by S-opsin in A second difference with the previous MEA study is that alignment of the preferred directions along the temporal and ventral quadrants were overrepresented [5,32], a bias that persisted in recordings from V1 at eye-opening [33] but was not seen here (Figure 2; Figure S3).…”
Section: Distribution Of Dsgc Preferred Directions Along the Cardinalcontrasting
confidence: 99%
See 4 more Smart Citations
“…In contrast to our results reported here, previous reports from our laboratory that were based on multi-electrode array (MEA) recordings indicated that the cardinal distribution of preferred directions was established at eye-opening [5]. One potentially important difference is that the current study was the use of light stimulation of cones dominated by S-opsin in A second difference with the previous MEA study is that alignment of the preferred directions along the temporal and ventral quadrants were overrepresented [5,32], a bias that persisted in recordings from V1 at eye-opening [33] but was not seen here (Figure 2; Figure S3).…”
Section: Distribution Of Dsgc Preferred Directions Along the Cardinalcontrasting
confidence: 99%
“…A second difference with the previous MEA study is that alignment of the preferred directions along the temporal and ventral quadrants were overrepresented [5,32], a bias that persisted in recordings from V1 at eye-opening [33] but was not seen here ( Figure 2; Figure S3). Interestingly, it was recently shown that DSGC preferred directions vary retinotopically (Sabbah, S., Gemmer, J., Castro, G., Siegel, J.…”
Section: Distribution Of Dsgc Preferred Directions Along the Cardinalcontrasting
confidence: 83%
See 3 more Smart Citations